Regulation of the Expression of the β-Lactam Antibiotic-Resistance Determinants in Methicillin-Resistant Staphylococcus aureus (MRSA) - Blázquez, Blas (2014)
β-Lactam antibiotics have faced obsolescence with the emergence of methicillin-resistant Staphylococcus aureus (MRSA). A complex set of events ensues upon exposure of MRSA to these antibiotics, which culminates in proteolysis of BlaI or MecI, two gene repressors, and results in the induction of resistance. We report studies on the mechanism of binding of these gene repressors to the operator regions by fluorescence anisotropy. Within the range of in vivo concentrations for BlaI and MecI, these proteins interact with their regulatory elements in a reversible manner, as both a monomer and a dimer.